Information technology law - Rowland, Diane (Routledge, 2012)
"This fourth edition of Information Technology Law has been completely revised in the light of developments within the field since publication of the first edition in 1997. Now dedicated to a more detailed analysis of and commentary on the latest developments within this burgeoning field of law, this new edition is an essential read for all those interested in the interface between law and technology and the effect of new technological developments on the law. New additions to the fourth edition include: - analysis of regulatory issues and jurisdictional questions - specific consideration of intermediary liability - developments in privacy and data protection - extension of computer crime laws - developments in software patents - open source software and the legal implications"--